The Administration of Cult in Hittite Emar - Cohen, Yoram (2011)
This paper discusses the administration of the cult in Emar during the period of Hittite rule over the city. It will be demonstrated that Hittite officials, with the cooperation of Emar citizens, mainly members of the Zū-Baʿla family, were deeply involved in the management of the cult. It will assess the data relating to the distribution of material and human resources, the registration of valuables belonging to temples, duties regarding sacrificial procedures, the installation of cultic personnel and the celebration of festivals and rituals. In conclusion an evaluation of the Hittites’ interest and involvement in the cults of Emar and its satellite cities is offered.
Keywords: administration in the Hittite Empire; Hittite officials; cult administration; the Zū-Baʿla family; Emar